Truth and metaphor in the thought of Nasr Hamid Abi Zaid: The contemporary secular Arab elite views the problem of religious truth - Bendjabbar, Abdallah (Journal of Human Sciences, 2022)
In this study, we deal with the problem of metaphor in the significance of the religious language, especially the significance of the qur’anic text, but in the conception of the late thinker nasr hamid abi zaid of religious truth, there is nothing but to prove his right to criticize the religious text, as - according to him - like literary texts that are accountable, perhaps he is lying in wait for the opposite truth of what the advocates of religious discourse reached. thus, we will discover the continuity of the historical record of owning religious truth, by adopting new contexts. that is, by focusing on the metaphor’s function and its limits in the contemporary circle of interpretation, then let’s look at what addition our thinker wanted regarding the topic.